2019
DOI: 10.1016/j.jsams.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of biomechanical risk factors for second and third metatarsal stress fractures in military recruits

Abstract: For second metatarsal stress fracture, aspects of foot type have been identified as influencing injury risk. For third metatarsal stress fracture, a delayed forefoot loading increases injury risk. Identification of these different injury mechanisms can inform development of interventions for treatment and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
22
0
3
Order By: Relevance
“…A later peak second metatarsal pressure during barefoot running was the strongest predictor of third metatarsal stress fracture risk in Royal Marines recruits [17]. This previous study found that in recruits who sustained a third metatarsal stress fracture, peak pressure occurred under the second metatarsal at 60% of stance, compared with 57% of stance in recruits who remained injury-free.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…A later peak second metatarsal pressure during barefoot running was the strongest predictor of third metatarsal stress fracture risk in Royal Marines recruits [17]. This previous study found that in recruits who sustained a third metatarsal stress fracture, peak pressure occurred under the second metatarsal at 60% of stance, compared with 57% of stance in recruits who remained injury-free.…”
Section: Discussionmentioning
confidence: 71%
“…The decision to use a barefoot running protocol in this study was based upon the recent identification of plantar loading variables as risk factors for stress fractures in this population, when using the same protocol [17,18]. Future investigation of changes in plantar loading during shod running and during load carriage whilst wearing military boots, would provide further insight into mechanisms for injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors determine how an individual responds to the repeated stresses that have the potential to increase the risk of a BSI. As a scientific community, we have identified many isolated BSI risk factors occurring in athletes and military personnel (Bennell et al, 1996(Bennell et al, , 1999Korpelainen et al, 2001;Lappe et al, 2001;Milner et al, 2006b;Kelsey et al, 2007;Pohl et al, 2008;Moran et al, 2013;Tenforde et al, 2013;Wright et al, 2015;Abbott et al, 2019a;Dixon et al, 2019;Nose-Ogura et al, 2019). However, risk factors do not exist in isolation.…”
Section: Introductionmentioning
confidence: 99%